Masail Fiqhiyyah Education on Hisab and Rukyat: Comparative Study of the Views of Nahdlatul Ulama and Muhammadiyah - Ulum, Miftahul; Aziz, Saiful; al-Hamidy, Abu Dzarrin; Muazzaroh, Faizatul; Achmad, Achmad; Nasiri, Nasiri (Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2026)
This study investigates the discourse of hisab and rukyat within masāʾil fiqhiyyah education by comparatively examining the perspectives of Nahdlatul Ulama (NU) and Muhammadiyah figures in East Java regarding the determination of the beginning of the Qamariyah month, particularly Shawwal. The research aims to analyze the ontological foundations, interpretative paradigms, and practical implications of both approaches in responding to contemporary developments in astronomy. This study employs a descriptive-comparative method with an astronomical-fiqh–fiqh approach. Primary data were obtained through in-depth interviews with NU and Muhammadiyah scholars in East Java. In contrast, secondary data were collected from organizational decrees, classical and contemporary fiqh texts, astronomical calculations, and relevant literature. The research was conducted in several regions of East Java. Data were collected through interviews, documentation, and literature review, and analyzed using qualitative comparative analysis supported by astronomical interpretation. The findings reveal that NU scholars predominantly prioritize ru’yah al-hilal supported by hisab. In contrast, Muhammadiyah scholars determine the Qamariyah month based on hisab with the wujud al-hilal criterion. The differences arise mainly from divergent interpretations of syar’i texts and outdated visibility criteria that are no longer consistent with modern astronomical science. Despite these differences, the study identifies the potential for reconciliation through the harmonization of criteria rather than the dichotomy of methods. The study concludes that integrating astronomical accuracy with fiqh interpretation is essential to resolving recurring polemics and strengthening rational Islamic legal discourse.